Antibiofilm potential of synthetic 2-amino-5-chlorobenzophenone Schiff bases and its confirmation through fluorescence microscopy. (September 2017) - Arshia,; Khan, Anum Khalid; Khan, Khalid Mohammed; Ahmed, Ayaz; Taha, Muhammad; Perveen, Shahnaz
Abstract: Antibacterial/antibiofilm potential of microwave-assisted synthetic thirty-three 2-amino-5-chloro benzophenone Schiff bases have been carried out against four bacterial strains i.e. Klebsiella pneumoniae, Proteus mirabilis, Staphylococcus aureus and Streptococcus mutans . Among them compounds5, 6, 8, 9, 14, 16, 22, 24, 26, and30 –32 showed antibiofilm activities against isolates at less than 100 μg/ml concentrations. These compounds showed enhanced antibiofilm activity against S. aureus as compared to cefixime used as control. However, remaining compounds were found to be active but at higher concentration. Fluorescence microscopy has been employed for confirmation of antibiofilm results. The structures of all synthetic molecules have been characterized on the basis of spectroscopic techniques including 1 H NMR, 13 C NMR, EI-MS, HREI-MS, and IR spectroscopy and their structure-activity relationship have been established. Graphical abstract: Highlights: Antibiofilm activity of synthesized compounds were performed. Fluorescence microscopy of selected compounds had been presented for biofilm inhibitory effect confirmation. Microwave assisted synthesis of 2-amino-5-chloro benzophenone Schiff bases were carried out.